Academic Stress and Language Proficiency: A Correlational Study - Mohammed, Fatin Uloom; Yahya, Nagham Q. (Journal of Tikrit University for Humanities, 2025)
Language proficiency depends on several factors. One of these factors is academic stress. Academic stress is now seen as a lifestyle dilemma. Students that are under a lot of academic stress have been known to experience behavioral issues, depression, anxiety, and other issues. The present study aims at finding out: 1-Iraqi EFL university students’ level of academic stress toward language proficiency. 2- The correlation between Iraqi EFL university students’ with academic stress and language proficiency. The total population of the study represents 300 college students who are studying in morning studies in the departments of English at the Colleges of Education of the universities of Tikrit and Samarra during the academic year 2023-2024. The sample of the present study is 160 third- year college students who are randomly selected from the department of English at the College of Education of the University of Tikrit. The study instruments include an academic stress questionnaire and language proficiency test. The language proficiency test is prepared and all instruments are submitted to specialists in the field of teaching English as a foreign language and linguistics to ensure its face validity. The reliability of the study instruments has been secured by using Alpha Cronbach method. The values obtained are satisfactory to ensure their reliability. Then, the study instruments are administrated to the sample students. T-Test of one coefficient and multiple regressions are used to analyze the data obtained and achieve the study aims. The major findings of this study can be summarized as follows: 1- It is concluded that Iraqi EFL university students have a low level of academic stress. 2- It was found that academic stress has a negative effect on language proficiency. In the light of the results certain conclusion are formulated, most important of which are: 1- Academic stress negatively impacts language proficiency. 2- Academic stress is a multidimensional concept that is especially present in educational environments.